PERANCANGAN APLIKASI AKADEMIK SISWA BERBASIS WEB RAUDHATUL ATHFAL (RA) RA MASHITOH 03 CILOPADANG (MAJENANG) - Riswanto, Beny; Salsabila, Khusna (Jurnal Teknologi dan Bisnis, 2019)
Internet as a center of information and communication among the public. By providing adequate convenience and flexibility, it is very helpful for promotion in the service sector and others. The author analyzes the running information system of RA MASHITOH 03. So that the Raudhatul Athfal application has been made, this is an application that can help parents and students to see the progress of their children's grades and payment of dues and can do online consultations without having to come directly to school. This application runs on the website and integrates with applications that are on the server using php and mysql, the admin is in charge of filling in grades to students which then the application will store student grade data which will be entered into the database. In this system the admin can also input payments student fees and answer consultations from parents regarding their children's problems. This application can also save costs compared to when parents come directly to school, which costs money and takes a long time to travel to school.